(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
The rise of digital pedagogies has redefined the contours of teaching and learning in the contemporary educational landscape. With the proliferation of online platforms such as Google Classroom, Moodle, Microsoft Teams, and Edmodo, the nature of teacher-student interaction, instructional design, and assessment practices has undergone significant transformation (Selwyn, 2016). This study examines how online learning platforms act as catalysts in enhancing teaching effectiveness by fostering teacher empowerment through improved access to instructional resources, increased pedagogical flexibility, and real-time engagement with learners (Trust, 2018). Grounded in the theoretical frameworks of Technological Pedagogical Content Knowledge (TPACK) and Bandura’s concept of self-efficacy, this research employs a mixed-methods approach to assess the relationship between digital platform integration and perceived teaching effectiveness (Mishra & Koehler, 2006; Bandura, 1997). Quantitative data from surveys administered to school and higher education faculty, complemented by qualitative interviews, reveal that teachers who receive sustained digital training and institutional support demonstrate higher instructional confidence and adaptability (Ertmer & Ottenbreit-Leftwich, 2010). The study also highlights that empowered teachers are more likely to incorporate collaborative, student-centred methods and data-driven decision-making into their practice.